Physical Activity, Health Status and Risk of Hospitalization in Patients with Severe Chronic Obstructive Pulmonary Disease - Benzo, Roberto P. (S. Karger AG, 2010)
BACKGROUND: Chronic obstructive pulmonary disease (COPD) is a leading cause of death and 70% of the cost of COPD is due to hospitalizations. Self-reported daily physical activity and health status have been reported as predictors of a hospitalization in COPD but are not routinely assessed. OBJECTIVES: We tested the hypothesis that self-reported daily physical activity and health status assessed by a simple question were predictors of a hospitalization in a well-characterized cohort of patients with severe emphysema. METHODS: Investigators gathered daily physical activity and health status data assessed by a simple question in 597 patients with severe emphysema and tested the association of those patient-reported outcomes to the occurrence of a hospitalization in the following year. Multiple logistic regression analyses were used to determine predictors of hospitalization during the first 12 months after randomization. RESULTS: The two variables tested in the hypothesis were significant predictors of a hospitalization after adjusting for all univariable significant predictors: >2 h of physical activity per week had a protective effect [odds ratio (OR) 0.60; 95% confidence interval (95% CI) 0.41–0.88] and self-reported health status as fair or poor had a deleterious effect (OR 1.57; 95% CI 1.10–2.23). In addition, two other variables became significant in the multivariate model: total lung capacity (every 10% increase) had a protective effect (OR 0.88; 95% CI 0.78–0.99) and self-reported anxiety had a deleterious effect (OR 1.75; 95% CI 1.13–2.70). CONCLUSION: Self-reported daily physical activity and health status are independently associated with COPD hospitalizations. Our findings, assessed by simple questions, suggest the value of patient-reported outcomes in developing risk assessment tools that are easy to use.